The Contextualization of Islamic Education: Reformulation the Essence and Urgency in the Islamic Educators in Information Transformation Era - Syukron, Buyung (Jurnal Pendidikan Islam, 2017)
Education is the way to prepare the next generation with excellence and competitiveness and Islamic education is no exception. Islamic education, which aims to form the perfect man (insan kamil), is faced with complicated problems of globalization era characterized by the transformation of information. Islam must dominate the quality of education, to be both resistant and flexible with the times. To form a solid Islamic education takes various steps. Reconstruction of the essence and urgency of Islamic education is a way to drown out the dichotomy of science, since all sciences, according to Islam, comes from one authority. The concept of pluralism education should be done so that Muslims are not conflicted in the belief of monopolistic practices. By understanding and accepting diversity, the nature of tolerance and inclusivity have been more mature so that Muslims are able to exchange thoughts for future progress. The term "reconstruction" in this paper indicates that there has been an existing paradigm used in Islamic education. However, this paradigm must now be designed or renewed so that Islamic education is able to build a democratic, religious, innovative, and ready person to face the challenges of the transformation of great and rapid information.